Recontructing Islamic Pedagogy: A Critical Analysis of Traditional and Modern Teaching Approaches - Putranta Cahaya Sampurna; Putri Nur Jannah (LP3M Pascasarjana STAI Ibnurusyd, 2025)
Islamic pedagogy has a long history rooted in classical scientific traditions and has evolved along with the progress of the times. This study critically analyzes traditional and modern teaching approaches in Islamic education, focusing on relevance, effectiveness, and challenges in their implementation. The research method used is a literature review with a descriptive qualitative approach. The results of the study indicate that traditional approaches such as talaqqi and sorogan are still relevant in shaping character and deep understanding of religious knowledge, but face challenges in adapting to the needs of the times. Meanwhile, modern approaches based on technology and interactive methods offer innovative solutions, but need to be integrated with Islamic educational values ​​so as not to lose their essence. This article recommends a hybrid approach that combines the advantages of both methods to improve the effectiveness of learning in contemporary Islamic education.